Investigation of the effects of welding variables on the welding defects of the friction stir welded high density polyethylene sheets - BİLİCİ, MUSTAFA KEMAL (SAGE PUBLICATIONS LTD, 2022)
Modern thermoplastic materials are used in an expanding range of engineering applications, such as in the automotive industry, due to their enhanced stress-to-weight ratios, toughness, a very short time of solidification, and a low thermal conductivity. Recently, friction stir welding has started to be used in joining processes in these areas. There are many factors that affect weld performance and weld quality in friction stir welding (FSW). These factors must be compatible with each other. Due to the large number of welding variables in friction stir welding processes, it is very difficult to achieve high strength FSW joints, high welding performance, and control the welding process. Welding variables that form the basis of friction stir welding; machine parameters, tool variables, and material properties are divided into three main groups. Each welding variable has different effects on the weld joint. In this study, friction stir welds were made on high density polyethylene (HDPE) sheets with factors selected from machine parameters and welding tool variables. Although the welding performance, quality, and strength gave good results in some conditions, successful joints could not be realized in some conditions. In particular, welding defects occurring in the combination of HDPE material with FSW were investigated. Welding quality, defects, and performances were examined with macrostructure. In addition, the tensile strength values of some the joints were determined. The main purpose of this study is to determine the welding defects that occur at the joints. The causes of welding defects, prevention methods, and which weld variables caused were investigated. Welding parameters and welding defects caused by welding tools were examined in detail. In addition, the factors causing welding defects were changed in a wide range and the changes in the defects were observed.
Keywords: friction stir welding of polymer; weld defect of plastic; welding parameters and tool design of FSW; processing technology; ACRYLONITRILE-BUTADIENE-STYRENE; MECHANICAL-PROPERTIES; PARAMETERS; MORPHOLOGY; STRENGTH; PLATE; TOOL